Experiencing the impossible and creativity: a targeted literature review - Richard Wiseman; Caroline Watt (PeerJ, 2022)
Previous work suggests that unexpected and surprising experiences (e.g., living in another culture or looking at surreal images) promotes creative thinking. This targeted literature review examines whether the inherent cognitive disruption associated with experiencing the seemingly impossible has a similar effect. Correlational and experimental research across six domains (entertainment magic, fantasy play, virtual reality and computer gaming, dreaming, science fiction/fantasy, and anomalous experiences) provided consistent support for the hypothesis. In addition, anecdotal evidence illustrated the possible impact that the creative output associated with each of these areas may have had on technology, science, and the arts. It is argued that impossible experiences are an important driver of creative thinking, thus accounting for reports of such experiences across the lifespan and throughout history. The theoretical and practical implications of this work are discussed, along with recommendations for future research.